2012
DOI: 10.4103/1319-2442.100943
|View full text |Cite
|
Sign up to set email alerts
|

PEComa of the urinary bladder

Abstract: Perivascular epithelioid cell tumors are a family of related mesenchymal neoplasms that include angiomyolipoma, lymphangiomyomatosis, clear cell sugar tumor of the lung and a group of rare morphologically and immunophenotypically similar lesions that show immunoreactivity for both melanocytic (HMB-45 and/or melan-A) and smooth muscle (actin and/or desmin) markers. This case is presented for its rare occurrence and characteristic morphologic and immunohistochemical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A search of the English literature indicated that only 12 previous cases of PEComas of the urinary bladder have been reported thus far [11-20], whereas two cases mentioned in Chinese-language literatures with English-language abstract were excluded because of the unavailable detail information [21,22]. The clinicopathologic features of all published cases of this kind of lesion are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of the English literature indicated that only 12 previous cases of PEComas of the urinary bladder have been reported thus far [11-20], whereas two cases mentioned in Chinese-language literatures with English-language abstract were excluded because of the unavailable detail information [21,22]. The clinicopathologic features of all published cases of this kind of lesion are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…To date, non-AML/non-LAM/non-CCST PEComas have progressively been documented in a variety of anatomical sites, such as visceral organs, soft tissue and bone [3-10]. However, only 12 cases of PEComas of the urinary bladder have been documented in the English-language literature worldwide [11-20]. Herein, we present a urinary bladder lesion occurring in a Chinese adolescent.…”
Section: Introductionmentioning
confidence: 99%
“…Angiomyolipoma belongs to a family of neoplasms called perivascular epithelioid cell tumors (PEComas) [1][2][3][4][5][6][7][8]. The World Health Organization (WHO) defines PEComas as ''mesenchymal tumors composed of histologically, ultra structurally, and immunohistochemically distinctive perivascular epithelioid cells C [9].…”
Section: Introductionmentioning
confidence: 99%
“…The management has been variable, but local resection appears to be curative for patients with benign tumours. A few patients were managed with TURBT alone and did not require further surgical intervention 7 8 11. There are several reports of PEComas of the bladder treated successfully with partial cystectomy 7 10 12 13 17 18 21.…”
Section: Discussionmentioning
confidence: 99%